Enzymatic hydrolysis of sea rough fish - Nhi, Tran Thi Y; Le Thi Thanh, Ha; Do Truong, Thien (Vietnam Journal of Science and Technology, 2023)
In this stuty, sea rough fish were hydrolyzed with alcalase/peptidase combined enzymes (EA/EP). Response surface methodology (RSM) was employed to optimize the EA/EP, hydrolysis time, hydrolysis temperature, and enzyme to substrate ratio (E/S) to obtain a high hydrolysis degree. The optimum RSM operating conditions were EA/EP of 2.9, temperature 55.8oC, incubation time of 4.9 h, and substrate concentration at 0.45 %. Under these conditions, DH value of 56.2 % was obtained. Raw materials proximate composition, amino acid content of the hydrolysate was also evaluated. The results indicated that sea rough fish contains potentially valuable fraction with high protein content and were successfully converted into hydrolysates rich in essential amino acids for potential recommendations in the supplementation of animal and human diets.